High current field test of impulse transient characteristics of substation grounding grid. Issue 16 (10th January 2019) - Tong, Xuefang; Dong, Xiaohui; Tan, Bo
Abstract : It is significant to research the impulse characteristics of substation grounding grid for its optimal design and safe and stable operation. In order to obtain the impulse transient characteristics of substation grounding grid under lightning impulse current more accurately, the impulse current field test was done on a real substation grid. By monitoring the impulse grounding impedance, impulse coefficient, longitudinal current, and node potential under different test conditions, impulse characteristics curves and the effect of some influence factors are gotten, then the main zones of current dispersion and voltage drop are proposed, as well as the effective areas under different conditions are proposed combined with simulation analysis. The results show that: the impulse grounding impedance and impulse coefficient are smaller when the current is injected from the central of the grid. The main current dispersion region of the large‐scale grounding grid is about 40 m around the injection point. The potential drops about 30% within 20 m around the injection point, and the change of the potential is small in the far distance. The effective area of substation grounding grid is affected by soil resistivity, and its side length is usually only tens of meters.